Distinct Effects of Body Mass Index and Waist/Hip Ratio on Risk of Breast Cancer by Joint Estrogen and Progestogen Receptor Status: Results from a Case‐Control Study in Northern and Eastern China and Implications for Chemoprevention. (4th December 2017) - Wang, Fei; Liu, Liyuan; Cui, Shude; Tian, Fuguo; Fan, Zhimin; Geng, Cuizhi; Cao, Xuchen; Yang, Zhenlin; Wang, Xiang; Liang, Hong; Wang, Shu; Jiang, Hongchuan; et al.
Abstract: Background: Obesity is a consideration in the pharmacologic intervention for estrogen receptor (ER) positive (ER+) breast cancer risk. Body mass index (BMI) and waist/hip ratio (WHR) have demonstrated different effects on breast cancer risk in relation to estrogen receptor (ER) status, but the results have been inconsistent. Furthermore, the situation in Chinese women remains unclear. Materials and Methods: We conducted a case‐control study including 1, 439 breast cancer cases in Northern and Eastern China. Both ER and progesterone receptor (PR) statuses were available for 1, 316 cases. Associations between body size‐related factors and breast cancer risk defined by receptor status were assessed by multiple polytomous unconditional logistic regression analysis. Results: Body mass index and WHR were positively associated with overall breast cancer risk. Body mass index was positively associated with both ER+/PR positive (PR+) and ER negative (ER−)/PR negative(PR−) subtype risks, although only significantly for ER+/PR+ subtype. Waist–hip ratio was only positively correlated with ER−/PR− subtype risk, although independent of BMI. Body mass index was positively associated with risk of ER+/PR+ and ER−/PR− subtypes in premenopausal women, whereas WHR was inversely correlated with ER+/PR− and positively with ER−/PR− subtype risks. Among postmenopausal women, WHR >0.85 was associated with increased risk of ER−/PR− subtype. Conclusion: Both general and central obesity contribute to breast cancer risk, with different effects on specific subtypes. General obesity, indicated by BMI, is more strongly associated with ER+/PR+ subtype, especially among premenopausal women, whereas central obesity, indicated by WHR, is more specific for ER−/PR− subtype, independent of menopausal status. These results suggest that different chemoprevention strategies may be appropriate in selected individuals. Abstract : Obesity is a consideration in the pharmacologic intervention for estrogen receptor‐positive breast cancer risk. This case‐control study among women in Northern and Eastern China was conducted to clarify the possible associations between both general and central obesity and breast cancer risk.